PENGARUH STRES KERJA,DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PERAWAT PUSKESMAS RANTAU PANJANG KIRI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Saputra Candra; Marzolina Marzolina; Rama Rovanita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of Work Stress, work discipline andmotivation on the performance on the performance of nurse in Rantau PanjangLeft Health Center, Kubu Babussalam sub-district, Rokan Hilir Regency.. Thepopulation in this study were all nurses at the Rantau Panjang Left Health Centeras many as 63 people. Sampling using the census method, namely taking theentire population as the research sample. The data analysis used is descriptiveanalysis, with quantitative analysis tools, namely multiple linear regression withthe help of the SPSS program. Based on the test results, it was found that thevariables of Work Stress, work discipline and motivation had a positive andpartially significant effect on nurse performance. The results of the F test alsoshow that the variables of Work Stress, work discipline and motivation have apositive and significant effect simultaneously on nurse performance. Keywords: Work stress, Work Discipline, Motivation and Employee Performance